A Patient‐Centered Approach to Hemodialysis Vascular Access in the Era of Fistula First. Issue 2 (12th January 2016) - Kalloo, Sean; Blake, Peter G.; Wish, Jay
Abstract: The primary vascular access options for the hemodialysis population are arteriovenous fistulas (AVF), arteriovenous grafts, and cuffed central venous catheters (CVC). AVFs are associated with the most favorable outcomes with respect to complications, interventions required to maintain functionality and patency, and overall cost. These population‐based outcomes, in conjunction with the efforts of the Fistula First Breakthrough Initiative, have propelled the prevalence of AVFs in the US hemodialysis population. While this endeavor remains steadfast in assuring the continued dominance of this policy for AVF preference, it fails to take into account a subset of the dialysis population who will fail to see the benefits of an AVF. This subset of patients may include the elderly, those with poor vasculature anatomy, those with slowly progressive CKD who are more likely to die than progress to ESRD, and those with an overall poor long‐term prognosis and shortened life expectancy. Thus, in an effort to avoid numerous unnecessary surgical and interventional procedures with minimal to no gains in clinical outcomes, an individualized patient approach must be adopted. The Centers for Medicare and Medicaid Services–instituted quality incentive program is designed to reward high AVF prevalence while also penalizing high CVC prevalence. The current model is devoid of case‐based adjustment, thus penalties are disbursed to dialysis providers in accordance with a "one‐size‐fits‐all" fistula only approach. The most suitable access for a patient remains the one that takes into account the characteristics unique to the individual patient with a primary focus on patient comfort, satisfaction, quality of life, and clinical outcomes.